Sistem Informasi Absensi Menggunakan Kamera GPS Berbasis Android di Auto2000 - Fifi Lailasari Hadianastuti; Denny Riandhita Arief Permana; Febry P.J. Sibuea; Salsabila Muharona Yuna (Jurnal Ilmiah Sains dan Teknologi, 2025)
Auto2000 BP Sunter is one of the companies in the automotive sector. Its attendance system still uses cards to record the daily presence of its workers. Based on these, an information system for managing the presence of workers is developed. This information system uses using android-based GPS Camera, that records the presence of workers, easily finding historical data to be assessed, evaluated, or analyzed. The developing system method used in this writing is the Waterfall method, with Javascript as the tool for programming with react-native framework, and Firebase as the tool for managing the database. In modeling the system, a diversity of diagrams in UML is used. ERD is also used for designing the database. With this Android-based GPS camera for presence information system, Auto2000 BP Sunter has been made easy to manage their data of employee attendance.